Determinants of cerebral collateral circulation in acute ischemic stroke due to large vessel occlusion - Sperti, Martina; Arba, Francesco; Acerbi, Amedeo; Busto, Giorgio; Fainardi, Enrico; Sarti, Cristina (Frontiers in Neurology, 2023)
Introduction: Cerebral collateral vessels have a central role in ischemic stroke pathophysiology, and they are considered to correlate with infarct size, success of reperfusion therapies, and clinical outcome. Our aim is to study factors influencing the development of collateral vessels in patients with acute ischemic stroke eligible for endovascular treatment. Materials and methods: We enrolled patients with acute ischemic stroke and large vessels occlusion of anterior circulation potentially eligible for endovascular treatment. Included patients performed multiphase CT angiography to identify the cerebral collateral vessels that were graded by Menon Score. We investigated the associations between clinical factors and cerebral collaterals and tested independent associations with logistic (good vs poor collaterals) and ordinal (collateral grade grouped, Menon 0-2, 3, 4-5) regression analysis adjusting for age, sex, stroke severity, onset-to-CT time (OCTT). Results: We included 520 patients, mean age was 75 (±13.6) years, 215 (41%) were males, median (IQR) NIHSS was 17 (11-22). Good collaterals were present in 323 (62%) patients, and were associated with lower NIHSS (median 16 vs 18; p<0.001), and left hemisphere involvement (60% vs 45%; p<0.001); whereas previous stroke/TIA was more frequent in patients with poor collaterals (17% vs 26%; p=0.014). These results were confirmed in both logistic and ordinal regression analysis where good collaterals were associated with lower NIHSS (OR= 0.94; 95% CI= 0.91-0.96; cOR= 0.95; 95% CI= 0.92-0.97, respectively), and left hemisphere stroke (OR=2.24; 95% CI=1.52-3.28; cOR=2.11; 95% CI=1.46-3.05, respectively), while previous stroke/TIA was associated with worse collaterals (OR=0.57; 95% CI=0.36-0.90; cOR=0.61; 95% CI=0.40-0.94, respectively). Vascular risk factors, demographics, and pre-stroke treatments did not influence the collateral score. Discussion: The results of our study suggest that risk factors and demographics do not influence the development of collateral circles, except for a negative relation with previous ischemic events. We confirm an already reported observation of a possible protective effect of collaterals on tissue damage assuming NIHSS as its surrogate. The association between left hemispheric stroke and better collaterals deserves to be further explored. Further efforts are needed to find factors able to favor collaterals development.